Electrochemical Tests to Evaluate the Stability of the Anodic Films on Dental Implants - C. E. B. Marino; L. H. Mascaro (International Journal of Electrochemistry)
The stability of anodic films potentiodynamically grown on titanium, titanium-grade 2, and Ti6Al4V alloy was studied in a simulated physiological electrolyte, up to 8.0 V, and at room temperature to determine the corrosion resistance levels of dental implants. In PBS (phosphate buffer saline) solution, thin titanium oxide films protect the surface of the Ti6%Al4%V alloy up to 6.0 V, pure Ti up to 8.0 V, and Ti-grade 2 up to 1.5 V. At more positive potentials, localized corrosion starts to occur possibly due to the alloy elements (Ti6Al4V-V and Al) and variable levels of interstitials (Ti-grade 2: C, N, and Fe, mainly). When the biomaterials were submitted to open-circuit conditions, in artificial saliva, the worst corrosion resistance was observed in dental implant (Ti-grade 2), according to the open-circuit potential values and reconstruction rate analysis of these oxide films. The XPS spectra revealed TiO2 oxide as the main phase in the barrier oxide film coating the dental implant.